2016
DOI: 10.1590/1518-8345.0784.2771
|View full text |Cite
|
Sign up to set email alerts
|

Support for learning in the perspective of patient safety in primary health care

Abstract: Objective: to analyze the support for learning, in the perspective of patient safety, offered in the work environment, according to health professionals working in primary care. Method: a transversal study, held with 86 health professionals working in primary care. A validated instrument was used, applied via the Internet. Descriptive statistical analysis was undertaken with a presentation of median, mean, standard deviation and coefficient of variation. Results: points which are favorable to supporting learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
0
12
0
6
Order By: Relevance
“…Authors point out that more experienced professionals can help with the work routine and contribute to the performance of younger colleagues in the team. This relationship favors communication, teamwork, exchange of knowledge and experiences, a fact that will culminate in strengthening the safety culture (20) . A study showed that doctors presented significantly higher scores than nurses in relation to patient safety (12) .…”
Section: Resolvabilitymentioning
confidence: 99%
“…Authors point out that more experienced professionals can help with the work routine and contribute to the performance of younger colleagues in the team. This relationship favors communication, teamwork, exchange of knowledge and experiences, a fact that will culminate in strengthening the safety culture (20) . A study showed that doctors presented significantly higher scores than nurses in relation to patient safety (12) .…”
Section: Resolvabilitymentioning
confidence: 99%
“…This could be again due to lack of staff development activities to improve their knowledge and skills in quality as shown by the scarcity of attendance of such training among them. In congruence with this, a study in Brazil highlighted the importance of staff development activities in enhancing nurses" performance related to patient safety (Paranaguá et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…26 Diante dos resultados apresentados e considerando que a APS é caracterizada como a porta de entrada do sistema de saúde e que tem a premissa de resolver cerca de 85% dos problemas da população, seus profissionais devem ter uma atuação assertiva de modo a prevenir a ocorrência de eventos adversos. 27 Ressalta-se que para a prevenção de riscos é necessário identificar e analisar a sua origem, bem como sistematizar as medidas preventivas de forma proativa e, não somente, quando os erros acontecem. Estabelecer uma sistemática de gerenciamento de riscos é um caminho para a busca de melhor controle e monitoramento dos processos de trabalho.…”
Section: Discussionunclassified